The Correlation Between Sense of Community Towards Parents Who Had Down Syndrome Children - Lestari, Endah; Mahanani, Fatma Kusuma (Utan Kayu Publishing, 2022)
Every parent wants to have the child they want. Parents want to have children who are perfect physically, mentally, and spiritually. But in reality not all parents have this opportunity, in some cases, there are some of them who have children who experience mental retardation such as Down syndrome. One of the factors that influence the caregiver's burden is social support, where social support can be provided by a community. This research is a correlational quantitative research. This objective of the study was to determine whether there is a correlation between a sense of community and the burden of caregivers on parents who have children with Down syndrome. The population in this study were parents who had children with Down syndrome. The sample in this study amounted to 142. The sampling technique in this study was carried out by purposive sampling technique. The instrument used in this study was a caregiver burden scale consisting of 38 items (31 valid items and 7 invalid items) with a reliability coefficient of 0.873 and a sense of community scale consisting of 34 items (30 valid items and 4 invalid items). Reliability coefficient was 0.915. The results of calculations with data processing software, obtained a sense of community is in the high category and caregiver burden is in the low category. Hypothesis testing was carried out using the Spearman correlation formula resulting in a rho value of -0.473 with a significance value of 0.000. Thus the hypothesis which reads that there is a negative correlation between sense of community and caregiver burden on parents who have children with Down syndrome is accepted. The higher the sense of community, the lower the caregiver's burden. Vice versa, the lower the sense of togetherness, the higher the caregiver's burden. Setiap orang tua pasti mendambakan memiliki anak yang sesuai dengan yang mereka idam-idamkan. Para orang tua ingin memiliki anak yang sempurna baik secara fisik, mental, maupun rohani. Namun pada kenyataannya tidak semua orang tua memiliki kesempatan tersebut, pada beberapa kasus, ada sebagian dari mereka ditakdirkan memiliki anak yang mengalami retardasi mental seperti down syndrome. Salah satu faktor yang mempengaruhi caregiver burden adalah dukungan sosial, dimana dukungan sosial dapat diberikan oleh suatu komunitas. Penelitian ini merupakan penelitian kuantitatif korelasional. Penelitian ini bertujuan untuk mengetahui apakah ada hubungan antara sense of community dengan caregiver burden pada orang tua yang memiliki anak down syndrome. Populasi dalam penelitian ini adalah orang tua yang memiliki anak down syndrome. Sampel dalam penelitian ini berjumlah 142. Teknik pengambilan sampel dalam penelitian ini dilakukan dengan teknik purposive sampling. Instrumen yang digunakan dalam penelitian ini berupa skala caregiver burden yang terdiri dari 38 aitem (31 aitem valid dan 7 aitem tidak valid) dengan koefisien reliabilitas sebesar 0,873 dan skala sense of community yang terdiri dari 34 aitem (30 aitem valid dan 4 aitem tidak valid) dengan koefisien reliabilitas sebesar 0,915. Hasil perhitungan dibantu dengan software pengolah data, diperoleh sense of community berada pada kategori tinggi dan caregiver burden berada pada kategori rendah. Uji hipotesis dilakukan dengan formula korelasi Spearman menghasilkan nilai rho sebesar -0,473 dengan nilai signifikansi 0,000. Dengan demikian hipotesis yang berbunyi ada hubungan negatif antara antara sense of community dengan caregiver burden pada orang tua yang memiliki anak down syndrome diterima. Semakin tinggi sense of comunity, maka semakin rendah caregiver burden. Begitu juga sebaliknya, Semakin rendah sense of community, maka semakin tinggi caregiver burden.